Improved Indonesian Language Learning Outcomes Material Intrinsic Elements of Stories through Video Media for Class IV Students - Septi Dwi Harmini (Universitas Sebelas Maret, 2020)
The purpose of this study was to improve the learning outcomes of students in the Indonesian muple material of the intrinsic elements of stories in grade IV elementary schools through audio-visual media in the form of video media. The research conducted was a three-cycle Classroom Action Research (CAR). The stages of each cycle are planning, implementing, observing and reflecting. Each cycle a post test is held to determine the development of students. The initial condition before the action was carried out, the data obtained from the students who had completed was 36.8%. In the first cycle, students who completed after carrying out the post test were 52.6%. In the second cycle students who completed after carrying out the post test were 84.2%. In the third cycle students who completed after carrying out the post test were 94.7%. These results indicate that video media can improve student learning outcomes, especially Indonesian muple material, the intrinsic elements of stories at SD Negeri 1 Tirip